A Systematic Review of Assistive Technology for Individuals With Intellectual Disability in the Workplace. Issue 1 (March 2018) - Morash-Macneil, Virginia; Johnson, Friggita; Ryan, Joseph B.
Research has shown that assistive technology (AT) can help support employment skills for individuals with intellectual disabilities (IDs). The authors of this review examined the effectiveness of various types of AT support for individuals with ID in the workplace with a focus on the participant's independent ability to demonstrate a specific employment skill. Ten articles published between 2006 and 2016 met inclusionary criteria set forth for this review. Overall, AT support resulted in medium to highly effective effect size gains (PND 91%; standardized mean difference 2.84; Tau-U 0.902), indicating effects were generally meaningful. Findings from these studies indicate AT was successful for increasing work performance of individuals with ID in respect to productivity, navigation, time management, and task completion. This review also provides an analysis of findings, discussion on limitations, and recommendations for future research.